Unsteady flow measurement around human hand in swimming using PIV - Matsuuchi, K.; Miwa, T.; Nomura, T.; Sakakibara, J.; Shintani, H.; Ungerechts, B. E. (Book of Abstracts - 9th Annual Congress European College of Sport Science, July 3-6, 2004, Clermont-Ferrand, France, 2004)
Much effort has been done for the estimation of propulsive force of swimmers in front crawl. The estimation was based essentially on quasi-steady flow theory. Flow fields around a self-propelling swimmer, however, are extremely unsteady (Ungerechts et al., 2003). In general unsteady flow force is greater than the steady one. Accordingly the quasi-steady analysis may give an underestimation of force (Toussaint, 2003). Flow visualisation will lead to a deeper understanding of the effects of unsteady flow condition around a self-propelling swimmer. In this experimental study in a flume the flow around the hand of a crawl swimmer was investigated. Main questions were: "Around hands Is the flow set into rotation as vortex?" and "How strong is the intensity of rotating water, called orticity, with respect to the unsteady dynamics?" Methods The underwater action of crawl swimmers` hands, swimming in a flume (test section: 4.6 x 2.0 x 1.5 m) at about 1.2 m/s, was searched and analysed. Unsteady velocity fields were measured using PIV (Particle Image Velocimetry) in several horizontal planes. The images were captured by a CCD camera set from below the test section using a mirror. Our PIV system can get 14 planes per second. A hundred of time-sequential flow fields can be obtained at once. Each flow field was calculated in terms of two particle images with the cross-correlation method. Results PIV can be used to detect the unsteady flow condition around a self-propelling swimmer. Although the flow is very complex, it is obvious that the flow near the hand is characterized by a locally strong vortex near the finger rotating clockwise and one far from a hand rotating anti-clockwise (Fig. 1.) The vorticity is coloured red if it rotates anti-clockwise (defined as positive sign) and blue it rotates clockwise (defined as negative sign). It should here be noted that the vector plot is fogged by halation resulting from a strong laser and also the effect of shadow of fingers. Taking this aspect into account, the data were analysed. Discussion/Conclusion In estimating the fluid force, it is important to know the location of vortex as well as its intensity. Our PIV system could detect the unsteady flow fields around a self-propelling swimmer. The position of vortices and their intensity were identified together with a position of a hand. This result helps us to estimate the magnitude of propulsive force.